FREQUENCY OF HEPATITIS C VIRUS IN PATIENT WITH LICHEN PLANUS PRESENTING TO TERTIARY CARE HOSPITAL IN KHYBER PAKHTUNKHWA, PAKISTAN - ZEB, S; ZEB, L; MEHMOOD, Z; KHAN, ZU; BASIT, A (Biological and Clinical Sciences Research Journal, 2023)
Lichen Planus (LP) is a chronic inflammatory condition that affects the skin, mucous membranes, or both. The present study aimed to determine the frequency of hepatitis C virus in patients with lichen planus. This cross-sectional study was conducted at the Department of Medicine, Medical Teaching Institute, Lady Reading Hospital Peshawar. The study duration was from July 2021 to December 2021. A thorough medical history and a comprehensive physical examination were obtained, including an evaluation of the affected skin and mucous membrane areas. A consultant dermatologist took Skin biopsies from the lichen planus lesions and sent them to the hospital laboratory for histopathological analysis. Hepatitis C virus infection was confirmed through PCR testing in the hospital laboratory. All collected data was documented on a specially designed form containing demographic information. The data was then analyzed using the Statistical Package for the Social Sciences (SPSS), version 23. Post-stratification chi-square tests were applied, with a significance level set at p ≤ 0.05 to determine statistical significance. In this study, we included a total of 101 patients who had lichen planus. The ages of these patients ranged from 18 to 50 years, with a mean age of 36.410 years and a standard deviation of 9.362 years. Among these patients, 23.8% were found to be infected with the Hepatitis C virus. The patients' mean Body Mass Index (BMI) was 25.78 kg/m2, with a standard deviation of 4.087 kg/m2. An interesting finding was a statistically significant association (with a p-value of 0.002) between BMI and the occurrence of Hepatitis C virus among lichen planus patients. This suggests a positive significant association between BMI and the presence of HCV in patients with lichen planus. These findings highlight the importance of considering age, gender, and BMI when assessing the risk of HCV infection in lichen planus patients. Furthermore, the relatively high prevalence of HCV among lichen planus patients in this population emphasizes the importance of regular screening for Hepatitis C in individuals with lichen planus, particularly in the fifth decade of life, and those with lower BMIs. This information may improve clinical management and patient care in lichen planus and its potential comorbidities.